The impact of the use of smart phones and social communication site (Facebook) as a means of educational assistance in the level of learning some offensive skills in wrestling of Judo - Tariq, Audi (Journal of Physical Education, 2014)
The research included five sections, the first section included the importance of research, and mention to the problem (the difficulty of some of the skills, and the required more hours in their education, and set a goal to search (the effect of using smart phones and social networking site (Facebook) means of educational assistance in the level of learning some offensive skills in wrestling of judo, and suppose the advantage of learning using educational methods proposed level of assistance, said areas of research. The second section has included theoretical studies regarding the subject, and in the third chapter, the researcher to research methodology and field procedures, where the research methodology mentioned a experimental method with the three groups, then the research sample and details view and method selected, then the male devices and tools used to search, the way conducting skill tests, at the end of this section researchers said that they used statistical methods in the search. Four of the research's sections presented the results obtained through them and the analyzed and discussed. In five section, researcher offer conclusions that got them through the analysis and discussion of the results that appeared identical to the assumptions set by the researcher and finally the researchers mention some of the recommendations that came on the basis of the researcher concluded, including the need to use modern technology as an aid in the educational process